舌癌に対する逆行性超選択的動注化学放射線療法119例における栄養摂取状況の分析 - 陳, 雪霏; 小栗, 千里; 石川, 聡一郎; 大橋, 伸英; 光藤, 健司; 林, 雄一郎; 竹田, 敦; 小泉, 敏之; 大屋, 貴志; 來生, 知 (日本口腔外科学会雑誌, 2024)
Purpose: We performed definitive concurrent chemoradiotherapy with retrograde superselective intra-arterial infusion (IACRT) for patients with advanced oral cancer who refused to undergo surgery. Although IACRT has excellent antitumor effects, it is associated with several acute adverse events, especially significant oral mucositis and radiation dermatitis, which often result in difficulty in food ingestion. In this study, we report on the outcomes of 119 patients with advanced tongue cancer, adverse events related to ingestion and swallowing, changes in dietary intake and nutritional status over time, and factors influencing dietary intake in this population. 　Materials and methods: A total of 119 patients (stage Ⅱ and Ⅲ, 47 cases; stage Ⅳ, 72 cases) with tongue cancer who had received IACRT between January 2008 and December 2018 were included in this study. The adverse events, Functional Oral Intake Scale (FOIS), and Onodera-Prognostic Nutritional Index (O-PNI) were assessed before and after treatment. Factors affecting FOIS after three months of treatment were also subjected to multivariate analysis. 　Results: The median follow-up period was 52 months. Grade 3 or 4 oral mucositis was observed in 92％ of the patients and radiation dermatitis in 41％ of the patients. The median FOIS was 6 before treatment, 1 immediately after treatment, 6 at three months after treatment, and 7 at one year after treatment. The FOIS differed significantly before treatment and three months after treatment. However, there was no significant difference between before treatment and six months after treatment. Multivariate analysis revealed that the radiation dose was an independent factor influencing FOIS at three months. O-PNI was 47.2 ± 6.3 before treatment, 34.4 ± 4.5 immediately after treatment, and 42.9 ± 9.2 at three months after treatment, with a significant difference between before and immediately after treatment, and no significant difference between before treatment and three months after treatment. 　Conclusion: Patients treated with IACRT had difficulty in dietary intake during treatment, however they were gradually able to eat as they did before treatment. After three months of treatment, the nutritional status of patients was equivalent to that before treatment. Moreover, after six months of treatment, dietary intake tended to be equivalent to that before treatment.